Pharmacy Technician Workload and Human Resources Requirements at MOH Hospitals during Nine years Mass Gathering Hajj (2006-2014) in Al-Medina Region, Saudi Arabia - Alomi, Yousef Ahmed; Alhennawi, Khairat; Khayayt, Nizar (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the pharmacy technician workload analysis and workforce requirements at Ministry of Health Hospitals during mass gathering Hajj nine years (2006-2014) in Al-Medina Region, Saudi Arabia. Methods: It is a retrospective of nine years (2006-2014) of hospital pharmacy technician workload during mass gathering Hajj period. The duration of workload collection was 15-30 days each year. The pharmacists provide pharmaceutical to all patients either Pilgrim or not Pilgrim at Medina region. The workforce requirements calculated based on MOH workforce standards per bed and the workload drives as central pharmacy technician services, patient specific pharmacy technician activities, and general administration specific pharmacy technician activities. Results: The total number of Pilgrims (1,952,817-3,161,573) with average (2,445,208). The total number of prescriptions was (22,278-133,107) with an average of (78,955). It represented (1.07-5.02%) with an average (3.11%) of all pilgrims. The total average number of pharmacy technician needed in Al-Madina was (69.2 FTE) per hospital. It divvied into (3.21FTE) for inpatient services per hospital, (11.48 FTE) for Emergency services per hospital, and (54.51FTE) for Ambulatory care services per hospital. The average number of pharmacy technician calculated per hospital was (38.47 FTE), while the mean number pharmacy technician needed to base on workload for all services was (69.20 FTE) per hospital. Conclusion: The pharmacy technician workforce’s analysis showed high demand during mass gathering Hajj over past several years despite clinical pharmacy technician missed. Aiming to increase workforce of pharmacy technician is potential to improve pharmacy services during mass gathering Hajj period in Al-Madina, Saudi Arabia.
Keywords: Pharmacy Technician; Workload; Workforces; Mass Gathering; Hajj; Al-Medina; Ministry of Health; Saudi Arabia